Investigação de elementos de transposição em populações de Drosophila mojavensis e D. arizonae e seus híbridos - Carnelossi, Elias Alberto Gutierrez [UNESP] (2014)
This thesis aimed to investigate how transposable elements (TEs), sequences capable of moving into the host genome and between different species, behave in interspecific hybrids. We seek to understand the activity of TEs in crosses between Drosophila mojavensis and D. arizonae due to some particular characteristics of this species pair. They are sister species, with very recent divergence ( < 1 million years ), present incomplete pre- and post- zygotic reproductive isolation in laboratory and one of them, D. mojavensis, had its genome sequenced, which allowed for in silico analyses of TEs. The thesis is divided into four chapters. The first presents a detailed analysis of an non- LTR retrotransposon called I, known to cause hybrid dysgenesis in D. melanogaster. Putatively active sequences similar to the I element were identified and characterized in the genome of D. mojavensis. The performed phylogenetic analyzes showed that the I sequences in D. mojavensis and those harbored by other Drosophila species belong to different I families. Expression analyses by RTq-PCR showed that this element is transcriptionally active in ovaries and testes of both species and their hybrids, and have high expression in the testes, but not in the hybrids ovaries, which could be associated with the male hybrid sterility phenotype. In the second chapter are presented analyses of expressed TEs in the ovaries of two parental strains and their hybrids by RNA-Seq. The results show species-specific expression of TEs in the parents and hybrids; and, in an unprecedented manner, that TEs are generally regulated in hybrids regarding with their parents, although some of them are overexpressed. In the third chapter are presented results of expression of four retrotransposons (Helena , I, Copia and Osvaldo) quantified by RTq-PCR; and finally, in the last chapter, we presented estimates of the genome size ( C - value), in both parental species and reciprocal hybrids ...